Absence of those Affected: Decision-Making Process for Reparations for the Dam Collapse in Brumadinho (Global Journal of Human-Social Science, 2025)
This article analyzes the decision-making process regarding reparations for the socio-environmental disaster resulting from the collapse of Vale s dam in Brumadinho in 2019 with the aim of answering the following question How did the decision-making process that produced the reparation agreement for the dam collapse in Brumadinho signed between Vale and the state of Minas Gerais come about And with what results To this end the procedural theory of democracy is used with an emphasis on Adam Przeworski s definition of democracy as the result or the combined play of institutions and resources
Keywords: decision-making processes; democratic deficit; socio-environmental disasters; dam collapse; court settlement